Selection of The Best Lecturer Using Fuzzy Tahani - Ilmiyah, Nur Fadilatul; Resti, Nalsa Cintya (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This quantitative descriptive study seeks to provide an overview of the Fuzzy Tahani use to aid in selecting the best lecturers in the Mathematics Education Study Program based on EDOM. Four areas of lecturer competency will be measured: pedagogical, professional, personality, and social. Compiling domains and membership functions, establishing membership degrees, compiling Fuzzy rules, compiling Fuzzy Queries, assessing fire strength, and assembling recommendations for the best lecturer candidates are the six parts of this research. The study's findings indicate that Fuzzy Tahani can aid in selecting the finest lecturers based on EDOM. Based on calculations, DTM06 is the best lecturer in the Mathematics Education Study Program.